Case-Based Reasoning Research and Development 24th International Conference, ICCBR 2016, Atlanta, GA, USA, October 31 - November 2, 2016, Proceedings - Goel, Ashok; Díaz-Agudo, M Belén; Roth-Berghofer, Thomas (Lecture Notes in Artificial Intelligence,, 2016)
This book constitutes the refereed proceedings of the 24th International Conference on Case-Based Reasoning Research and Development, ICCBR 2016, held in Atlanta, GA, USA, in October/November 2016. The 14 revised full papers presented were carefully reviewed and selected from 44 submissions. The papers cover a wide range of CBR topics that are of interest both to researchers and practitioners from foundations of Case-Based Reasoning; over CBR systems for specific tasks and related fields; up to CBR systems, applications and lessons learned in specific areas of expertise such as health; e-science; finance; energy, logistics, traffic; game/AI; cooking; diagnosis, technical support; as well as knowledge and experience management.